Diseño de un sistema de generación eléctrica a partir de fuentes renovables de energía fotovoltaica para la empresa “quevexport s. a.” en el cantón Quevedo. - Figueroa Guerra, Danner Anderson (2020)
This document aims to show an analysis that underscores the productivity and efficiency of a photovoltaic generation system (PV) in the Canton "QUEVEDO", in the company" QUEVEXPORT S.A.". A system proposal for electricity generation is proposed to meet the demand required by that company (network connection system), seeking to reduce negative impacts on the environment. Nasa Power provides data on renewable resources over a period of time, including the most relevant is solar radiation, indispensable for the design of the FV plant. Cost, efficiency and productivity sizing and analysis is done using HOMER Energy software, a very useful tool for designing projects in the area of renewable energy and hybrid generation systems. In order to have a better analysis with respect to results, the Sunny software was used to corroborate the results of Homer and to have a respective check, besides that we will have an analysis of results with respect to the profitability factor to see if there is any difference of investment in the corresponding analyses in each software. The purpose of this project is to determine an efficient and reliable system with the aim of reducing the consumption problems faced by large companies due to the use of large machines, in order to provide a better service, these machines generate a very high load curve at the end of the month. Keywords: Efficiency, productivity, cost analysis, renewable resources, efficiency analysis